Genetic heterogeneity in hereditary haemorrhagic telangiectasia: possible correlation with clinical phenotype. Issue 12 (December 1994) - McAllister, K A; Lennon, F; Bowles-Biesecker, B; McKinnon, W C; Helmbold, E A; Markel, D S; Jackson, C E; Guttmacher, A E; Pericak-Vance, M A; Marchuk, D A
Abstract : Hereditary haemorrhagic telangiectasia (HHT) or Osler-Weber-Rendu syndrome is an autosomal dominant vascular dysplasia characterised by recurrent haemorrhage. Our initial linkage studies found an HHT gene to be localised to 9q3 in two large kindreds. In the present study, we examine an additional five unrelated HHT families. Linkage analysis in this region resulted in a peak multipoint location score of 13.03, 10 cM proximal of D9S60. We found significant evidence for heterogeneity of HHT. Multipoint analysis supports the family specific two point studies with odds of 3, 000, 000:1 showing linkage and heterogeneity over linkage and homogeneity. Four of the seven families give a posterior probability of > 99% of being of the linked type, and three families appear unlinked to this region of 9q, and by multipoint analysis completely exclude the candidate region for HHT. Two new crossovers in affected persons in one of the linked families further define the proximal border of the candidate region on 9q3. A possible correlation in clinical phenotype between the 9q3 linked families and unlinked families is described. Although six of the seven families clearly meet the clinical criteria for HHT diagnosis, a significant absence of pulmonary arteriovenous malformations is seen in all three 9q3 unlinked families. Genetic heterogeneity of HHT and its potential correlation with a clinical phenotype may have a significant impact on the clinical management and treatment of HHT patients.